Управління посередницькою діяльністю митних брокерів на ринку митних послуг в Україні - Горошков, Богдан Олегович; Goroshkov, Bohdan Olehovych (Ірпінь, 2024)
У роботі розроблено та обґрунтовано теоретичні положення і методичні підходи регулювання посередницької діяльності митних брокерів на ринку митних послуг в Україні

The work developed and substantiated theoretical provisions and methodical approaches to the regulation of intermediary activities of customs brokers on the market of customs services in Ukraine
Management of intermediary activities of customs brokers in the market of customs services in Ukraine
Keywords: митний брокер; посередницька діяльність; митні послуги; customs broker; intermediary activities; customs services